A novel health indicator for a linear motion guide based on the frequency energy tracking method. (August 2022) - Kim, Seokgoo; Cho, Seong Hee; Ryu, Haeyong; Choi, Joo-Ho
Highlights: A novel health indicator (HI) for a linear motion (LM) guide is proposed to monitor the condition from the early stage. Two pipelines for the proposed method are suggested depending on the existence of run-to-fail data for industrial applications. Natural faults made by run-to-fail experiments are used to demonstrate the performance of the proposed HI. Abstract: Linear motion (LM) guides are widely used to provide linear motion in manufacturing lines. To prevent the economic loss derived from unexpected failures, the health condition of an LM guide should be monitored in real time. For this purpose, a novel method for health indicator (HI) construction is proposed in this study based on frequency energy tracking (FET), which is motivated by the energy concentration phenomena over cycles in the frequency domain. The FET method can identify frequency bands that exhibit degradation characteristics, and convert them into the HI to detect anomalies and monitor fault progression over time. Depending on the availability of run-to-failure data, the method suggests two approaches, one for quantitative health assessments and remaining life prediction against the failure threshold, and the other for anomaly detection and the qualitative monitoring of fault progression.